2021
DOI: 10.1038/s41562-021-01212-7
|View full text |Cite
|
Sign up to set email alerts
|

Why lockdown and distance learning during the COVID-19 pandemic are likely to increase the social class achievement gap

Abstract: The COVID-19 pandemic has forced teachers and parents to quickly adapt to a new educational context: distance learning. Teachers developed online academic material while parents taught the exercises and lessons provided by teachers to their children at home. Considering that the use of digital tools in education has dramatically increased during this crisis, and it is set to continue, there is a pressing need to understand the impact of distance learning. Taking a multidisciplinary view, we argue that by makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(199 citation statements)
references
References 112 publications
3
132
0
4
Order By: Relevance
“…Moreover, confinement to home while studying may cause children’s mental health problems [ 5 , 6 ]. Thus, parents engage in their children’s home-based online learning, and also take on more supervision tasks than in offline learning [ 2 , 7 ]. Existing studies related to home-based online learning during the pandemic also call for parents to participate in their children’s learning and create a good learning environment for their children (e.g., [ 42 ]).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, confinement to home while studying may cause children’s mental health problems [ 5 , 6 ]. Thus, parents engage in their children’s home-based online learning, and also take on more supervision tasks than in offline learning [ 2 , 7 ]. Existing studies related to home-based online learning during the pandemic also call for parents to participate in their children’s learning and create a good learning environment for their children (e.g., [ 42 ]).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Many countries have adopted home-based online learning instead of face-to-face learning to reduce the spread of COVID-19 [ 1 ]. The shift from offline school learning to home-based online learning resulted in changes in the learning environment and amplified the parents’ role in children’s schoolwork [ 2 ]. During the epidemic, home-based online learning can prevent the spread of the virus in physical spaces [ 3 ], and it makes parents feel at ease because their children are in a safe environment at home.…”
Section: Introductionmentioning
confidence: 99%
“…School closures represent a huge challenge for parents, whose role in their children’s learning becomes even more essential than during normal times ( Goudeau et al, 2021 ). In the present research, we argued that, even if all parents were involved in homeschooling during school closures, important variations may emerge depending on the social-class position of the family.…”
Section: Discussionmentioning
confidence: 99%
“…This research demonstrated that the social class achievement gap that exists during the school year tends to grow during school breaks, particularly during summer holidays. More importantly, recent research shows that school closure has, indeed, enhanced the social class achievement gap during the first wave of the pandemic ( Andreu et al, 2020 ; Engzell et al, 2020 , for a synthesis, see Goudeau et al, 2021 ). Since academic success is usually claimed to be “meritocratic” ( Mijs, 2016 ; Darnon et al, 2018 ; Kuppens et al, 2018 ) and since it subsequently determines future occupations in society, the school system not only contributes to the reproduction of social inequalities but also to their legitimization ( Darnon et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation